2012
DOI: 10.1111/hex.12004
|View full text |Cite
|
Sign up to set email alerts
|

A design process for using normative models in shared decision making: a case study in the context of prenatal testing

Abstract: Background Shared decision making (SDM) encourages the patient to play a more active role in the process of medical consultation and its primary objective is to find the best treatment for a specific patient. Recent findings, however, show that patient preferences cannot be easily or accurately judged on the basis of communicative exchange during routine office visits, even for patients who seek to expand their role in medical decision making (MDM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The objective of the SDM process is to find the best treatment for a specific patient by encouraging the patient to play a more active role in the process of medical consultation [1]. Thus, eliciting patient preferences is a vital component of SDM [2].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the SDM process is to find the best treatment for a specific patient by encouraging the patient to play a more active role in the process of medical consultation [1]. Thus, eliciting patient preferences is a vital component of SDM [2].…”
Section: Introductionmentioning
confidence: 99%
“…Patient advocacy and shared decision making (i.e., collaborative decision making that balances the provider’s expert knowledge with the patient’s right to be fully informed) have been promoted in health care settings when health care decisions are being made (Padgett et al, 2014; Rapaport, Leshno, & Fink, 2014; Segal & Shahar, 2009). By contrast, this study revealed that the participants seemed to readily accept obstetricians’ recommendations for undergoing amniocentesis, and their spouses agreed to the wives’ decisions without objections.…”
Section: Discussionmentioning
confidence: 99%